2006
DOI: 10.1007/s10517-006-0313-y
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional study of the therapeutic effect of autologous mesenchymal stem cells in experimental diffuse brain injury in rats

Abstract: Effects of systemic transplantation of mesenchymal stem cells obtained by culturing of autologous bone marrow on proliferative activity of cells and functional morphology of neurons after diffuse brain injury were studied in Wistar rats. Comparative analysis of the results indicated that systemic injection of mesenchymal stem cells in a syngeneic organism produced proliferotropic, angiogenic, and, presumably, neurotrophic effects. The therapeutic effect visually manifested on day 2 after intravenous injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Relative rate of learning, % percent of rats with avoidance response success/failure Regression of sign increase, b coefficient very of damaged tissue and cell structures [4]. This effect of systemic transplantation of MSC on the process of structural reparation in the damaged area of rat brain can, in turn, determine more efficient recovery of the psychophysiological status of experimental animals observed in our study.…”
Section: Groupsupporting
confidence: 55%
See 1 more Smart Citation
“…Relative rate of learning, % percent of rats with avoidance response success/failure Regression of sign increase, b coefficient very of damaged tissue and cell structures [4]. This effect of systemic transplantation of MSC on the process of structural reparation in the damaged area of rat brain can, in turn, determine more efficient recovery of the psychophysiological status of experimental animals observed in our study.…”
Section: Groupsupporting
confidence: 55%
“…Published data suggest that bone marrow stromal cells significantly alleviate motor and neurological deficit in animals with traumatic brain injury [7]. Our previous studies showed that systemic administration of syngeneic MSC produces proliferotropic, angiogenic, and probably neurotrophic effects [4].…”
mentioning
confidence: 99%
“…Previous experiments showed that various types of SC, including bone marrow MSC [3,6,[21][22][23], umbilical blood SC [27,32,35], and NSC [8,9,11,15] (e.g., immortalized [10] and genetically modified lines of human NSC [18]), can induce the expression of growth and trophic factors, increase the proliferative activity, and contribute to functional recovery of the brain.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed on male Wistar rats weighing 140-160 g. CCT was produced by a 50-g weight, which fell on the parietal region of the head from a height of 110 cm [6]. Fifty percent rats died over the first 5 min after the incidence of trauma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation